SOCIAL BUSINESS: GAINING STEAM FROM THEORY TO PRACTICE - NJIE, ATHANA PRIESTLY VEKIMA (Innovare Journal of Social Sciences, 2021)
The world is faced with a multitude of pressing problems and needs such as hunger, poverty, disease, poor health care, homelessness, pollution, adverse climate conditions, and other environmental hazards, just to name a few. Volunteer work, charities, and donations and of course the traditional profit-making businesses with all the elegant economic theories surrounding them have not been able address these ills which are a serious plaque to the society. In a bid to satisfactorily reduce or put an end to these societal hazards, Muhammad Yunus, the 2006 Nobel Peace Prize Winner and the practical genius who pioneered microcredit with his Grameen Bank, has initiated what is today known as social business. Social business is a new kind of business, not for profits, that is dedicated to solving a particular social, economic, or environmental problem that has plagued mankind since time immemorial. The whole idea about social business is to improve the lives of people by harnessing the energy of profit making to the objectives of fulfilling basic human needs. The resounding success stories of the Grameen Bank, the very first social business created by Muhammad Yunus has paved the way for other organizations to follow suit. This paper has demonstrated how social business has moved from a mere theory to a practice undertaken by several organizations that is transforming lives and having the potential to redeem the failed promise of the free-market enterprise.